2017
DOI: 10.1111/acer.13410
|View full text |Cite
|
Sign up to set email alerts
|

Predischarge Injectable Versus Oral Naltrexone to Improve Postdischarge Treatment Engagement Among Hospitalized Veterans with Alcohol Use Disorder: A Randomized Pilot Proof‐of‐Concept Study

Abstract: Background Injectable naltrexone for alcohol use disorders (AUDs) has been efficacious in several studies. It has not been (1) compared head-to-head with oral naltrexone, or (2) examined in the hospital setting as an intervention that might facilitate treatment attendance after hospital discharge. Methods Fifty-four hospitalized veterans identified as having DSM-IV alcohol dependence were randomized to receive: (1) a 50 mg oral naltrexone plus a 30-day prescription, or (2) a 380 mg intramuscular naltrexone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…[40][41][42]45,48,62,63 One study assessed the effect of the combination of naltrexone with lofexidine with respect to naltrexone associated with placebo, and found that the combination with lofexidine was favorable with respect to craving control but did not provide improvements in abstinence from opioid use. 63 These results differ from some previously found. 10 In alcohol-consuming patients, despite having adherence rates around 50%, both oral NTX and XR have been shown to be safe and effective drugs in reducing alcohol consumption even in populations with comorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42]45,48,62,63 One study assessed the effect of the combination of naltrexone with lofexidine with respect to naltrexone associated with placebo, and found that the combination with lofexidine was favorable with respect to craving control but did not provide improvements in abstinence from opioid use. 63 These results differ from some previously found. 10 In alcohol-consuming patients, despite having adherence rates around 50%, both oral NTX and XR have been shown to be safe and effective drugs in reducing alcohol consumption even in populations with comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies included in this review, not all found significant differences. 40–42 , 45 , 48 , 62 , 63 One study assessed the effect of the combination of naltrexone with lofexidine with respect to naltrexone associated with placebo, and found that the combination with lofexidine was favorable with respect to craving control but did not provide improvements in abstinence from opioid use. 63 These results differ from some previously found.…”
Section: Discussionmentioning
confidence: 99%
“…Oral and injectable naltrexone show similar decreases in likelihood of binge drinking [65] and both are generally well tolerated, with fairly mild side effects [66]. Importantly, however, naltrexone does block the therapeutic effects of opioid analgesics and can precipitate opioid withdrawal in patients who have developed physical dependence to opioids [34]; therefore, individuals who are prescribed naltrexone for AUD must be monitored for opioid use and withdrawal.…”
Section: Naltrexone (Oral and Extended-release)mentioning
confidence: 99%
“…28 Similar efficacy between long-acting intramuscular (IM) naltrexone and oral naltrexone has been observed in small proof-of-concept studies, although no large-scale head-tohead comparisons have been performed. 32 Because naltrexone is especially effective in decreasing heavy drinking, it could be considered in highly motivated patients to be taken as needed in settings where they wish to consume alcohol but wish to avoid heavy drinking, although this has been less studied in humans. 33 Naltrexone is dosed 50 mg by mouth once daily or 380 mg via IM injection once monthly.…”
Section: Fda-approved Pharmacotherapymentioning
confidence: 99%